RANCANG BANGUN MEDIA FLASH CARD BERBASIS AUGMENTED REALITY MATERI BENTANG ALAM DI KELAS IV SEKOLAH DASAR - Salamah, Febri Nur; Chan, Faizal; Budiono, Hendra (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2026)
This study aims to develop augmented reality-based flashcard learning media on landform materials for fourth-grade elementary school students and to determine its validity and practicality. The research employed a Research and Development method using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. Preliminary observations were conducted at SDN 274/VI Muara Delang II to identify learning problems in IPAS, while product trials were carried out with fourth-grade students. Data were collected through validation sheets from media, content, and language experts, as well as questionnaires for teacher and student responses. Data were analyzed using quantitative and qualitative approaches. The results showed that the AR-based flashcard media obtained an average score of 4.6 from media experts, 4.6 from content experts, and 4.75 from language experts, all categorized as very valid. Practicality test results indicated that teacher responses reached an average score of 5.00 (very practical), while student responses in small-group and large-group trials were 4.42 and 4.59 respectively, both categorized as very practical. Therefore, the AR-based flashcard media is considered highly valid and practical, making it suitable for use in IPAS learning for fourth-grade elementary school students. ABSTRAK Penelitian ini bertujuan untuk mengembangkan media pembelajaran flashcard berbasis augmented reality (AR) pada materi bentang alam di kelas IV Sekolah Dasar serta mengetahui tingkat validitas dan kepraktisannya. Penelitian menggunakan metode penelitian dan pengembangan (Research and Development) dengan model ADDIE yang meliputi tahap analisis, desain, pengembangan, implementasi, dan evaluasi. Observasi awal dilakukan di SDN 274/VI Muara Delang II untuk mengidentifikasi permasalahan pembelajaran IPAS, sedangkan uji coba produk dilakukan pada siswa kelas IV. Teknik pengumpulan data meliputi lembar validasi ahli media, ahli materi, dan ahli bahasa, serta angket respon guru dan peserta didik. Data dianalisis secara kuantitatif dan kualitatif. Hasil penelitian menunjukkan bahwa media flashcard berbasis AR memperoleh nilai rata-rata validasi ahli media sebesar 4,6, validasi ahli materi sebesar 4,6, dan validasi ahli bahasa sebesar 4,75 dengan kategori sangat valid. Hasil uji kepraktisan menunjukkan respon guru memperoleh nilai rata-rata 5,00 dengan kategori sangat praktis, respon peserta didik pada uji coba kelompok kecil sebesar 4,42 dan kelompok besar sebesar 4,59 dengan kategori sangat praktis. Berdasarkan hasil tersebut, media flashcard berbasis augmented reality dinyatakan sangat valid dan sangat praktis sehingga layak digunakan sebagai media pembelajaran IPAS di kelas IV Sekolah Dasar.